Consumer Legal Protection Against Food Order Discrepancies on Digital Platforms Based on Electronic Agreements in Samarinda City - Nur Paridah Mey Yulia; Asnawi Mubarok; Rio Arif Pratama (CV Edujavare Publishing, 2026)
The development of information and communication technology in the digital era has brought fundamental changes in the patterns of economic interaction in society, especially in electronic-based trading activities (e-commerce). This is marked by the increasing use of digital platforms as transaction media, including in the online food ordering service sector. The purpose of this study is to analyze the legal status and force of electronic agreements in food ordering transactions on digital platforms in Samarinda City. To examine the form and division of responsibility of business actors and digital platform providers based on electronic agreements for consumer losses due to inconsistencies in food orders. This study uses an empirical legal research method with a sociological legal nature. In this study, an empirical approach is used to directly examine the practice of food ordering transactions through digital platforms in Samarinda City. The conclusion of this study is the position of electronic agreements in food ordering transactions on digital platforms regarding order inconsistencies is that electronic agreements have an important position in regulating the rights and obligations between consumers, platforms, and merchants. However, there are still shortcomings in consumer understanding of these electronic agreements. The form of responsibility of business actors and platforms for consumer losses due to inconsistencies in orders is that business actors and platforms have a responsibility to handle consumer complaints and provide solutions to inconsistencies in orders. However, there are still shortcomings in complaint handling, such as slow responses and inadequate compensation.